RISK ANALYSIS OF ORGANOCHLORINES ACCUMULATION IN HUMAN BREAST MILK (CASE STUDY: SUKAPURA VILLAGE, KERTASARI DISTRICT, BANDUNG REGENCY) - Moulfia Tursina, Lulu
Some of the types of organochlorines has been banned for used such as DDT, aldrin, dieldrin, endosulfan and heptachlor. Chronic exposure of organochlorines in humans within food chain can lead to the accumulation in the body which contains many lipids such as adipose tissue and breast milk. Particularly, infants are vulnerable to exposure of organochlorines on prenatal and postnatal stage. Various adverse health effects can occur, such as the long-term impact on intellectual function and delayed effects on the central nervous system function. The purpose of this study is to calculate the health risk of children, particularly infants, who consumed breast milk containing organochlorines residues. This risk analysis study was conducted in Sukapura village, Kertasari District, Bandung Regency From total 295 lactating mothers, the number of respondents who were included in this study were 30 mothers with certain criteria. Organochlorines accumulation measurement in breast milk conducted by EPA method 8081B using Gas Chromatography-Electron Capture Donor (GC-ECD). From 30 human breast milk samples, 28 samples contained organochlorines lindane, aldrin, heptachlor, DDT, dieldrin, endrin and endosulfan. 10 human breast milk samples of them have HI values > 1 which states that the human breast milk has the potential to harm the health of the infant. From 10 human breast milk samples, 6 of them are samples from mothers who breastfeeding the first child (primipara) and 4 are samples from mothers who breastfeeding the second child (multipara). The highest of HI values for primipara group was 4.691, while for multipara group was 1.965.